Mitigating the Urban Heat Island Effect in a Local Context : how wind and vegetation regulate temperatures during summer, with an example from the grounds of Karlstad Central Hospital, Sweden - Kirkhorn, Patricia (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2022)
Climate change is the cause of more weather extremes. Cities' dense configuration, heat absorbing surfaces and low amount of vegetation leads to higher temperatures within cities known as the urban heat island effect (UHI). Mitigating and adapting to warm temperatures is of great importance to minimise the risk of people suffering from heat stress and for avoiding high energy usage for cooling. This thesis researches how vegetation, especially trees, interacts with wind and solar radiation using Geographical Information Systems and microclimate modelling, with aim for greater understanding how to use nature based solutions within cities. The study takes place at the Karlstad region hospital area in Sweden. Scenarios with different amounts of trees and respective leaf area density were modelled in a unvegetated area enclosed with buildings on two sides. The results showed that vegetation slightly changes wind speed while the wind patterns are more affected by vegetation. Air temperature reduction is highest under the trees and its near surroundings. The result showed that the amount of trees matter; more trees evens out and lower temperatures in a wider area. Thus, the overall physiological equivalent temperature (PET), which considers the heat balance of the body, air temperature, incoming solar radiation, wind movement and humidity, found that wind and vegetation best together improves thermal comfort during warm seasons. This thesis illustrates the complex challenges in cities and the many interactions leading to higher temperatures. Understanding a place's prerequisites, meteorological conditions, vegetation aesthetic and technical functions is key for providing a long term sustainable design. Further research assessing more seasons and sites is suggested to evaluate the results viability.